2000
DOI: 10.1073/pnas.97.22.12109
|View full text |Cite
|
Sign up to set email alerts
|

Direct genetic demonstration of Gα13 coupling to the orphan G protein-coupled receptor G2A leading to RhoA-dependent actin rearrangement

Abstract: G2A is an orphan G protein-coupled receptor (GPCR), expressed predominantly in T and B cells and homologous to a small group of GPCRs of unknown function expressed in lymphoid tissues. G2A is transcriptionally induced in response to diverse stimuli, and its ectopic expression suppresses transformation of B lymphoid precursors by BCR-ABL. G2A induces morphological transformation of NIH 3T3 fibroblasts. Microinjection of constructs encoding G2A into Swiss 3T3 fibroblasts induces actin reorganization into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 35 publications
(31 reference statements)
2
63
1
Order By: Relevance
“…There are several lines of evidence that Mas, G2A, and PAR-1 transform NIH3T3 cells by activation of speci®c Rho family members (Kabarowski et al, 2000;Martin et al, 2001;Weng et al, 1998;Zohn et al, 1998bZohn et al, , 2000. First, we have observed that NIH3T3 cells that are transformed by these GPCRs, or by activated derivatives of Rho family members, form similar foci of transformed cells that are comprised of rounded, piled-up non-refractile cells.…”
Section: Par-1 G2a and Mas Transform By Activation Of Rho And Rac Prmentioning
confidence: 84%
“…There are several lines of evidence that Mas, G2A, and PAR-1 transform NIH3T3 cells by activation of speci®c Rho family members (Kabarowski et al, 2000;Martin et al, 2001;Weng et al, 1998;Zohn et al, 1998bZohn et al, , 2000. First, we have observed that NIH3T3 cells that are transformed by these GPCRs, or by activated derivatives of Rho family members, form similar foci of transformed cells that are comprised of rounded, piled-up non-refractile cells.…”
Section: Par-1 G2a and Mas Transform By Activation Of Rho And Rac Prmentioning
confidence: 84%
“…and O.N.W., unpublished observations, June 2003), its expression level is similar to G2A in the human THP-1 monocytic cell line and human primary monocytes and macrophages as measured by quantitative RT-PCR. 11 Although it has been shown previously that high level of G2A overexpression can exert some biologic activities without exogenous addition of ligand 37,38 or in a ligand-independent manner, 39 G2A-mediated cell chemotaxis is ligand-dependent. Overexpression of G2A alone is not sufficient to trigger cell migration in the absence of LPC ( Figure 2B).…”
Section: Org Frommentioning
confidence: 99%
“…Interestingly, it has been shown that G2A couples promiscuously with various G proteins during different biologic processes in different cell types. For example, G i coupling for calcium flux in MCF10A cells and extracellular signal-regulated kinase (ERK) activation in Chinese hamster ovary (CHO) cells, 17 G 13 coupling for stress fiber formation in fibroblasts, 38 G q and G 13 coupling for NF-B activation, and G s and G 13 coupling for apoptosis in Hela cells 39 all have been reported in these ectopic overexpression systems. While important for calcium flux and ERK activation, G i coupling is not required for LPC/G2A-mediated chemotaxis.…”
Section: G I -Independent Pathways In Cell Migrationmentioning
confidence: 99%
“…Certain G2A effects induced by ectopic overexpression of the receptor occurred in the absence of exogenously added ligand (4,(6)(7)(8). It is therefore possible that these effects are the manifestation of ligand-independent constitutive activation.…”
Section: The Chemotactic Effect Of Lpc On Do1110 Cells Does Not Appementioning
confidence: 99%
“…Introduction of G2A in these cells by retroviral transduction or microinjection induced significant morphological alterations, including suppression of contact inhibition, foci formation, and assembly of actin stress fibers (7). Genetic studies using embryonic fibroblasts derived from various G␣-deficient mice have demonstrated that G2A-induced cytoskeletal changes require coupling to G␣ 13 and subsequent activation of RhoA (7).…”
mentioning
confidence: 99%